A case report on a large, peduncular intra‐abdominal hepatocellular carcinoma extending into the retroperitoneum. Issue 3 (8th January 2021) - Omer, Dana M.; Dozier, Jordan; Cao, Zongxian; Zhu, Hongfa; McCain, Donald A.
Key Clinical Message: Here, we discuss a relatively uncommon presentation of a hepatocellular carcinoma and discuss its preoperative planning and surgical intervention required to reach complete resection. Abstract : Here, we discuss a relatively uncommon presentation of a hepatocellular carcinoma and discuss its preoperative planning and surgical intervention required to reach complete resection.